The Deterrent Power of Cartel Fines: An Assessment Based on Brazil’s Recent Experience - Adilson Santana de Carvalho; Sergio Goldbaum (Revista Direito GV)
Abstract Brazil’s Administrative Council for Economic Defense (Cade) has spent years discussing the effectiveness of calculation rules for pecuniary fines imposed on companies convicted in the trial proceedings of cartel cases. The core of this debate lies in the deterrent effects of the fines applied. This article analyzes a sample of 209 fines imposed by Cade on companies convicted of cartel behavior in 153 cases from 2012 to 2021. The analysis is based on economic theories of optimal deterrent fines and the economic rationality of offenses and penalties. The study compares the amounts of fines imposed by Cade, based on the selected sample, with those recommended by three theoretical models - Combe (2006), Combe and Monnier (2011) and Buccirossi and Spagnolo (2007) - in various scenarios. The analysis concludes that, in all the scenarios studied, the fines imposed by Cade fall short of what is necessary to achieve the expected deterrent effect on cartel behavior.